Tunnels - Gordon, Roderick; Williams, Brian James, 1958- (Sommerset : Chicken House, 2007)
When Will Burrows and his friend Chester embark on a quest to find Will's archaeologist father, who has inexplicably disappeared, they are led to a labyrinthine world underneath London, full of sinister inhabitants with evil intentions toward "Topsoilers" like Will and his father.
6.9
5-8.
5-8
Keywords: Adventure and adventurers -- Juvenile fiction; Archaeology -- Juvenile fiction; Underground areas -- Juvenile fiction; Adventure and adventurers -- Fiction; Archaeology -- Fiction; Underground areas -- Fiction; Adventure fiction; Archeology -- Fiction; Underground architecture -- Fiction; England -- Juvenile fiction; London (England) -- Juvenile fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction